Formulasi Gel dari Fraksi Etil Asetat Batang Jarak Cina (Jatropha multifida L.) Efektivitas Terhadap Luka Bakar - Giovana Zola, Elpa; Hartesi, Barmi; Anggresani, Lia (Journal of Pharmaceutical and Sciences, 2025)
Background: Burns represent a condition of damaged or lost skin tissue due to high-temperature exposure. Oral therapy has limitations in penetrating hardened skin tissue, necessitating topical preparations such as gels that offer advantages in comfort, absorption capability, and ease of application. The stem of physic nut (Jatropha multifida L.) contains bioactive compounds including alkaloids, flavonoids, saponins, and tannins that may accelerate burn wound healing, particularly in its ethyl acetate fraction. Objective: This study aimed to formulate the ethyl acetate fraction of physic nut stem into a gel preparation and evaluate the effect of concentration variations on burn wound healing efficacy. Methods: Physic nut stems were extracted with 96% ethanol, then fractionated using n-hexane, ethyl acetate, and ethanol solvents. The ethyl acetate fraction was formulated into a hydrophilic gel at concentrations of 0.140%, 0.281%, and 0.421%. The gel preparations were evaluated through organoleptic tests, homogeneity, pH, spreadability, stability, irritation, and burn healing efficacy tests in rabbits. Results: Phytochemical screening revealed that the ethyl acetate fraction contained alkaloids, flavonoids, saponins, and tannins. All gel formulations met physical preparation requirements with skin-compatible pH (5.95-6.37). Formula F1 (0.140%) demonstrated optimal burn healing efficacy, equivalent to positive control (p > 0.05), and was topically safe (non-irritating). Conclusion: The ethyl acetate fraction of physic nut stem was successfully formulated into a stable and effective gel preparation for burn wound healing, with 0.140% as the optimal concentration. Further studies are required to examine toxicity and the mechanism of action of active compounds.